Qué es el Dinero Digital de Bancos Centrales (CBDC)? Una introducción a sus principales características, oportunidades y riesgos potenciales - Sebastián Katz (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
– Digital transformation is provoking a real revolution in the payment's landscape of many economies in the last few years. New technologies and the change in public's habits are transforming not only the way payments are processed but the very modes of registering, storing and transferring value among economic agents. In that sense, a potential change in the forms of money as social convention or institution is also taking place. Many of these trends were accelerated by the pandemic. As a consequence of these developments, Central Banks started to actively explore the possibility of issuing their own digital monetary liabilities directed towards the general public, or retail CBDC (Central Bank Digital Currency). Many of them have progressed from conceptual research towards practical experimentation and a few jurisdictions have decided to implement it in the last period. This working paper presents a general overview of these efforts, the potential benefits that could derive from this initiative and the alternative designs and architectures under study oriented to minimize some of its risks.
Keywords: 330; Virtuelle Währung; Geldpolitik; Zentralbank; Welt